Composition of Petri Nets models in service-oriented industrial automation - J. Marco Mendes (2010)
In service-oriented systems, composition of services is required to build new, distributed and more complex services, based on the logic behavior of individual ones. This paper discusses the formal composition of Petri nets models used for the process description and control in service-oriented automation systems. The proposed approach considers two forms for the composition of services, notably the offline composition, applied during the design phase, and the online composition, related to the synchronization of Petri nets models on the fly. An experimental case study is used to illustrate the proposed composition approach.